2019
DOI: 10.1007/s10803-019-03889-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Sensory Profiles of Children on the Autism Spectrum Using the Short Sensory Profile-2 (SSP-2)

Abstract: Exploring the sensory profiles of children on the autism spectrum using the Short Sensory Profile-2 (SSP-2) This paper was amended after peer-review and accepted into Journal of Autism and Developmental Disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 28 publications
6
60
1
1
Order By: Relevance
“…In this study, it is observed that, in all categories of the instrument -Quadrants (Figure 1), Sensory and Behavioral Sections ( Figure 2) and School Factors (Figure 3) -, the classification of "More and Much More than the Majority of the Others" expresses the highest prevalence of classification, totaling, in all aspects evaluated by the instrument, 62.9%. This result corroborates the study carried out by Simpson et al (2019), in which it was identified that the participants had a rating of "More and Much More than the Majority of the Others" in all categories of the instrument, with the highest score being obtained in both studies.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, it is observed that, in all categories of the instrument -Quadrants (Figure 1), Sensory and Behavioral Sections ( Figure 2) and School Factors (Figure 3) -, the classification of "More and Much More than the Majority of the Others" expresses the highest prevalence of classification, totaling, in all aspects evaluated by the instrument, 62.9%. This result corroborates the study carried out by Simpson et al (2019), in which it was identified that the participants had a rating of "More and Much More than the Majority of the Others" in all categories of the instrument, with the highest score being obtained in both studies.…”
Section: Resultssupporting
confidence: 90%
“…In the Sensory Sensitivity quadrant, the percentage of students who had dysfunction in sensory processing, classified as "More and Much More than the Majority of the Others" represents 56.4%, data that corroborates the research carried out by Simpson, Adams, Alston-Knox, Heussler and Keen (2019), which identified sensory subtypes in children with ASD using the Sensory Profile 2, which was answered by the children's caregivers. The aforementioned study (Simpson et al, 2019) obtained a result similar to that of this study, considering that, from the parents' perspective, children with ASD presented a "More and Much More than the Majority of the Others" behavior in 65.7% of the cases, corroborating the perception of teachers analyzed in this research.…”
Section: Resultssupporting
confidence: 85%
“…In parallel to the above work, several studies have attempted to characterise heterogeneity in sensory features by identifying more homogeneous groups of individuals via different types of cluster analyses and latent class analyses (LCA) approaches (for a review see [30]). To date, studies have proposed anywhere from two to five subgroups using a range of different measures including the SSP [12,18,31], Sensory Experiences Questionnaire (SEQ [16]), Adolescent/Adult Sensory Profile (AASP [32]), Sensory Profile (SP [33]), Infant Toddler Sensory Profile (ITSP [34]) and Sensory Profile 2 (SP-2 [35,36]). These instruments differ widely in the type of informant (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The sensory seeking quadrant of the ITSP in the visual modality provides a measure of infants' active involvement in activities or actions such as looking at stimulating objects or attending to stimulating visual information (e.g., fast-paced TV). Although elevated seeking of restricted and repetitive stimulation is reported in toddlers and children with ASD by studies using the ITSP or other age-appropriate sensory questionnaires (SP and SSP;Dunn, 1999Dunn, , 2014 (Ben-Sasson et al, 2009;Lane et al, 2010;Liss et al, 2006;Simpson et al, 2019;Tomchek et al, 2018), decreased seeking is often documented in infants later developing ASD ( This evidence suggests that such sensory questionnaires may capture different constructs during early infancy as compared to later childhood. In particular, in early development, the ITSP visual sensory seeking items capture infants' drive toward novel and diversive visual input, rather than restricted and repetitive stimulation.…”
Section: Research Highlightsmentioning
confidence: 99%
“…For example, during early childhood, ASD has often been associated with increased behavioral (Baranek, Boyd, Poe, David, & Watson, 2007;Baranek, Foster, & Berkson, 1997) and neural response to sensory input (Kolesnik et al, 2019;Miyazaki et al, 2007), and decreased seeking of sensory stimulation (Beranova et al, 2017;Mulligan & White, 2012;Ben-Sasson et al, 2009;Tomchek & Dunn, 2007; but see Damiano-Goodwin et al, 2018). Conversely, during late childhood and adulthood, ASD has been linked to both increased and decreased behavioral (Ausderau et al, 2014;Rogers & Ozonoff, 2005) and neural response to sensory input (Cascio, Gu, Schauder, Key, & Yoder, 2015;Marco, Hinkley, Hill, & Nagarajan, 2011), and elevated seeking of restricted, repetitive, and often self-produced sensory stimulation (Ben-Sasson et al, 2009;Lane, Young, Baker, & Angley, 2010;Liss, Saulnier, Fein, & Kinsbourne, 2006;Simpson, Adams, Alston-Knox, Heussler, & Keen, 2019;Tomchek, Little, Myers, & Dunn, 2018).…”
Section: Introductionmentioning
confidence: 99%